초등학생의 수학 인식론적 신념과 시험불안의 관계에서 수학 시험준비전략의 조절효과 분석 - 유현석; 염시창 (한국초등수학교육학회지, 23(4), 2019)
이 연구의 목적은 초등학생의 수학 인식론적 신념과 시험불안의 관계에서 수학 시험준비전략의 조절효과를 검증하는데 있다. 이를 위해 수학 인식론적 신념을 예측변인, 수학 시험준비전략을 조절변인, 시험불안을 결과변인으로 설정하여 구조방정식 모형을 활용한 조절효과 검정을 시도하였다. 이 연구는 G광역시에 소재한 13개 초등학교 6학년 810명(남학생 411명, 여학생 399명)을 대상으로 수학 인식론적 신념 검사, 시험불안 검사, 수학 시험준비전략 검사를 실시하여 자료를 분석하였다. 분석 결과, 초등학생의 수학 인식론적 신념과 시험불안의 관계에서 수학 시험준비전략의 조절효과가 유의하였다. 즉, 수학 인식론적 신념이 높을수록 시험불안이 낮았고, 수학 인식론적 신념이 낮을수록 수학 시험준비전략 수준이 시험불안에 미치는 영향력이 큰 것으로 나타났다. 이 분석결과는 수학 인식론적 신념이 낮은 학생들의 경우 수학 시험준비전략에 대한 강조가 오히려 시험불안에 대한 영향력을 가중시키는 반면, 수학 인식론적 신념 수준이 높은 학생들에게는 수학 시험준비전략을 높이기 위한 노력이 시험불안을 낮추는데 효과적임을 시사한다. This study aimed to analyze the moderated effects of mathematics test-preparation strategies in the relation between elementary school students’ epistemological beliefs about mathematics and test anxiety. The moderated effects were tested by using structural equation modeling with the Ping’s two-step approach. The subjects were 810 6th graders (411 male, 399 female) from 13 elementary schools situated in G Metropolitan City. Tests for epistemological beliefs about mathematics, test anxiety, and mathematics test-preparation strategies were used as measurement scales. The results of this study were as follows. The moderated effects of mathematics test-preparation strategies in the relation between epistemological beliefs about mathematics and test anxiety were statistically significant. Higher level of epistemological belief about mathematics were linked to lower level of test anxiety, while lower level of epistemological belief about mathematics led to an increased influence of test-preparation strategies levels on test anxiety. Students who had higher levels of epistemological belief about mathematics displayed lower level of test anxiety when using high levels of test-preparation strategies. Students who scored lower in the epistemological belief about mathematics had lower level of test anxiety when employing low levels of test-preparation strategies. Therefore, to lower the level of test anxiety among elementary students, the intervention program need to consider the appropriate levels of test-preparation strategies in accordance with each student’s level of epistemological belief about mathematics. KCI Citation Count: 1